Electrostatic Self‐Assembly of Ag‐NPs Mediated by Eu3+ Complexes for Physically Unclonable Function Labels - Yao Kou; Yanan Guo; Lijuan Liang; Xue Li; Yifan Wang; Pingru Su; Chun‐Hua Yan; Yu Tang (Aggregate)
ABSTRACT Physically unclonable functions (PUFs) are essential for anticounterfeiting. Creating high‐stability, multimode, and secure labels remains challenging. Herein, we present a novel self‐assembly method for modulating the optical signals of rare‐earth (RE) complexes via interactions with Ag nanoparticles (Ag‐NPs). Initially, we engineered a positively charged Eu3+ complex ([EuL3]3+), which promotes the self‐assembly of negatively charged Ag‐NPs to form Eu/Ag‐NPs composites. The assembly of Ag‐NPs induces a surface plasmon effect that boosts the luminescent quantum yield and Raman signal intensities, and modifies the luminescence lifetime of the [EuL3]3+. Crucially, these micron‐scale Eu/Ag‐NPs can be applied to substrates, facilitating high‐resolution signal acquisition and diverse information encoding within limited space. Validation experiments reveal that PUF labels crafted using Eu/Ag‐NPs exhibit inherent randomness and uniqueness, along with stable and repeatable signal output. The strategic self‐assembly of Ag‐NPs, mediated by [EuL3]3+, along with the effective modulation of material properties, paves the way for advancing high‐resolution, high‐information‐density solutions in anticounterfeiting technologies.